Mapping Collectivism Research in Marketing: A Global Scopus Bibliometric Analysis - Yao, Lan; Salleh, Salniza Bt Md.; Kamaruddin, Nur Nadia Adjrina Binti (International Review of Management and Marketing, 2025)
Collectivism is a key cultural dimension that shapes consumer attitudes, particularly about sustainability and group identity. This study maps three decades of collectivist research in marketing and identifies key gaps in the field. Based on 631 English-language journal articles indexed in Scopus from 1996 to 2024, the analysis combines performance metrics with co-citation and keyword mapping using Biblioshiny and VOSviewer. Results show a steady growth in publication volume, with recent studies focusing more on green consumption and digital platforms. Despite this expansion, the literature remains heavily centered on Hofstede’s cultural dimensions, Triandis’s framework, and Fornell and Larcker’s measurement model, indicating persistent theoretical path dependence. Research is also geographically concentrated in the United States and China, with limited representation from Africa and Latin America. Emerging-market contexts and Gen-Z cohorts receive comparatively little attention. These findings suggest that future studies should develop more grounded models of collectivism in sustainability research and broaden regional coverage. For marketing practitioners, the results point to both the potential and limitations of leveraging collectivist values to promote eco-conscious behaviors across culturally diverse audiences.